2022
DOI: 10.3389/fcvm.2022.961760
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Ultrasound-Assisted endovascular therapy for carotid artery floating thrombus

Abstract: BackgroundCarotid free-floating thrombus (CFFT) is a rare but sometimes emergent condition. There has been controversy over the optimal treatment strategy. Emerging evidence suggests that endovascular thrombectomy (EVT) may be an alternative to surgery. Accurate alignment of the aspiration catheter and thrombus during EVT is critical but has, so far, remained unresolved.Case summaryThis is a rare case of CFFT presenting with acute right-sided facial droop and moderate dysarthria in a 77-year-old man. He was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Currently, there is insufficient data/evidence to compare the different procedural modalities in managing CFFTs. 6,7,10,13,14,[16][17][18]25,26 A retrospective study of 525 cases with CFFTs found no significant difference in outcomes of patients receiving antiplatelet and anticoagulant therapy versus procedural management with endovascular or surgical carotid endarterectomy (CEA). 5 With its minimally invasive nature and advanced modern catheters and devices, endovascular thrombectomy, as opposed to CEA, has become the preferred choice for the procedural management of CFFTs at many centers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Currently, there is insufficient data/evidence to compare the different procedural modalities in managing CFFTs. 6,7,10,13,14,[16][17][18]25,26 A retrospective study of 525 cases with CFFTs found no significant difference in outcomes of patients receiving antiplatelet and anticoagulant therapy versus procedural management with endovascular or surgical carotid endarterectomy (CEA). 5 With its minimally invasive nature and advanced modern catheters and devices, endovascular thrombectomy, as opposed to CEA, has become the preferred choice for the procedural management of CFFTs at many centers.…”
Section: Discussionmentioning
confidence: 99%
“…5 With its minimally invasive nature and advanced modern catheters and devices, endovascular thrombectomy, as opposed to CEA, has become the preferred choice for the procedural management of CFFTs at many centers. 6,25 Since the last major literature review conducted in 2019, 5 there have been an additional 27 cases managed with endovascular treatment in the literature. Although these reports have not demonstrated a standardized technique for the mechanical thrombectomy of CFFTs, numerous methods including stentrievers, reversal of carotid flow with occlusion balloons, and distal filter wire placement have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations